Análise de Microrredes Zero Carbono em Operação Ilhada - FIGUEREDO, Wender Martins (2024)
This master’s thesis explores the characteristics, operation, and challenges of microgrids powered 100% by renewable sources, including sizing, energy balance, and costs. An isolated zero-carbon microgrid is powered exclusively by renewable energy sources. It utilizes energy storage technologies, such as short-duration batteries or hydrogen storage, to mitigate intermittency and ensure a reliable power supply, allowing demand to be met even under conditions of low production or high variability. The asymmetry between generation and load over time has technical and economic implications for microgrid sizing. This asymmetry can be mitigated by combining renewable sources with varied intermittency profiles, impacting both the storage system and the sizing of the generating units to be installed. This thesis formulates the problem of sizing an isolated microgrid to meet all load requirements using exclusively renewable sources. The implications of this objective are analyzed and discussed, and sensitivity analysis studies are conducted to explore potential load-shedding agreements and their impact on the solution. Although the studies are conducted on a small-scale microgrid, the conclusions can be extended to systems of any scale.